THE IMPACT OF THE MAGNITUDE OF OVERHEAD COSTS ON THE DIFFERENCE BETWEEN ABC AND TDABC SYSTEMS - Tarzibashi, Omar Fikrat Fateh; Ozyapici, Hasan (Sciendo, 2019)
The objective of this study is to investigate the impact of the magnitude of overhead costs on the results of ABC and TDABC differences. A quantitative research method was used and data were gathered through an extensive literature review. A total of 170 articles that included both ABC and TDABC were found and 37 were used because only 37 articles included both the application of the systems and the comparison of the results of the systems. Correlation analysis and regression analysis were used to test whether there is a relationship between overhead costs and the differences in the results of ABC and TDABC systems. The results indicated that there is a statistically significant relationship between the total amount of overhead cost and the differences in the results of ABC and TDABC systems. Accordingly, when the overhead costs are increased, the TDABC system produces more different results than ABC. Based on this finding, the practical implication of this study seems to portray that companies with high overhead costs using the TDABC system rather than the ABC have the advantage of ascertaining product costing differently, which are more accurate.
Keywords: activity-based costing system; advanced costing systems; correlation analysis; overhead; regression analysis; time-driven activity-based costing system